Use of Sludge Waste as Ingredient in Making of Brick - Amsayazhi, P; Saravana Raja Mohan, K (International Journal of Engineering and Technology, 2018)
Waste may be defined as an unwanted material generated after the manufacturing process from industry, agriculture, or from house hold activity. Waste causes many nuisances in the environment. It produces many types of infection, for human and animal. The sludge from tannery effluent plants has problem of disposal. Dewatered sludge is disposed off by land filling. However, it is not an appropriate solution, due to the land limitation. The production of sludge in tannery effluent plant is about to increase every year. In addition, the constraint to treat sludge is very high in cost and time-consuming, which is the disadvantage to the responsible parties. Therefore, this study was carried out to utilize those sludge waste (SW) produced from the tannery effluent plant as a brick. The sludge brick (SB) mixtures were incorporated with many ratios of SW. Tests were conducted such as fineness test, specific gravity, water absorption and compressive strength. As the conclusion, brick with 20% utilization of SW is acceptable to produce good quality of brick. This study shows that the disposal of tannery sludge TSW would act as a suitable material for manufacturing of bricks with proportionate mix and design.